Electrode design for aluminium ion batteries - Chin, Zhi Xuan (Nanyang Technological University, 2022)
The advent of Aluminium-Ion Batteries (AIBs) has garnered more attention for its perceived ability to substitute the market-dominant Lithium-ion Batteries (LIBs), drawing from the fact that Aluminium (Al) has higher valency than Lithium (Li), and how AIBs are a safer energy source. One variety of AIBs is the rechargeable Aqueous Aluminium-ion Batteries (AAIBs). Studies have been done to compare the different cathode materials used in AAIBs and proved that the use of Manganese (Mn) based electrodes can lead to better performance. One possible way to tune the performance of AAIBs could be by incorporating key elements used in the very successful LIBs as part of a new electrode design for AAIBs. This study shows that Fe is a good dopant choice as it moderately improves discharge voltage with good stability, but at the expense of low capacity retention and efficiency. Co shows a slight improvement in capacity retention with comparable efficiency as the undoped cathode, while Ni does not appear to have any major effect.